Three-Dimensional Nonlinear Seismic Response of Immersed Tunnel in Horizontally Layered Site under Obliquely Incident SV Waves - Xiaojie Zhou; Qinghua Liang; Yueyu Zhang; Zhongxian Liu; Ying He (Shock and Vibration)
A three-dimensional (3D) detailed numerical model of an immersed tunnel in a horizontally layered site is established in this study. The 3D seismic response of the immersed tunnel in a horizontally layered site subjected to obliquely incident waves is analyzed based on the precise dynamic stiffness matrix of the soil layer and half-space via combined viscous-spring boundary and equivalent node stress methods. The nonlinear effects of external and internal site conditions on the whole model were determined by equivalent linearization algorithm and Mohr–Coulomb model, respectively. The proposed model was then applied to investigate the nonlinear seismic response of an immersed tunnel in the Haihe River subjected to seismic waves of oblique incidence. The dislocation (opening) of pipe joints in the immersed tunnel were analyzed to determine the response characteristics of the shear keys and overall displacement of the tunnel; the dynamic responses of the immersed tunnel subjected to obliquely incident seismic waves markedly differ from those of vertically incident seismic SV waves. The maximum stress value of shear keys and the maximum dislocation of the pipe joint appear as upon critical angle. The overall displacement of the tunnel increases as incident angle increases. Under severe earthquake conditions, both the pipe corners and midspan section of the roof and floor are likely to produce crack. These areas need careful consideration in the seismic design of immersed tunnel structures.